MiR‐206 inhibits the growth of hepatocellular carcinoma cells via targeting CDK9. (21st September 2017) - Pang, Chi; Huang, Gang; Luo, Kaili; Dong, Yuying; He, Fengtian; Du, Guankui; Xiao, Man; Cai, Wangwei
Abstract: miR‐206 plays an important role in regulating the growth of multiple cancer cells. Cyclin‐dependent kinase 9 (CDK9) stimulates the production of abundant prosurvival proteins, leading to impaired apoptosis of cancer cells. However, it is unknown whether CDK9 is involved in the miR‐206‐mediated growth suppression of hepatocellular carcinoma (HCC) cells. In this study, we found that the expression level of miR‐206 was significantly lower in HCC cell lines than that in normal hepatic cell line (L02). Meanwhile, CDK9 was upregulated in HCC cell lines. Moreover, miR‐206 downregulated CDK9 in HCC cells via directly binding to its mRNA 3′ UTR, which resulted in a decrease of RNA PolII Ser2 phosphorylation and Mcl‐1 level. Additionally, miR‐206 suppressed the cell proliferation, and induced cell cycle arrest and apoptosis. Similarly, silence or inhibition of CDK9 also repressed the cell proliferation, and induced cell cycle arrest and apoptosis. Taken together, the results demonstrated that miR‐206 inhibited the growth of HCC cells through targeting CDK9, suggesting that the miR‐206‐CDK9 pathway may be a novel target for the treatment of HCC. Abstract : miR‐206 inhibits the growth of hepatocellular carcinoma cells via targeting CDK9. These data indicated that miR‐206 plays its anti‐HCC effect via, at least partially, targeting the CDK9 signaling pathway, suggesting that miR206‐CDK9 pathway may be a novel potential target for the treatment of HCC.